Experimental research on arc characteristics for a 40.5‐kV vacuum circuit breaker. Issue 16 (1st March 2019) - Zhan, Xiaohan; Liu, Xiaoming; Li, Longnv; Zhu, Gaojia; Li, Peiyuan
Abstract : With the proposal and development of the energy internet, the wind power generation techniques, the photovoltaic power generation and the fuel cell, the power generation technology has been further developed and applied on a large scale. The vacuum switch, as one of the core components of the power system, is researched and manufactured to control and protect the grid system. Due to the changes of the external parameters during the development of the vacuum switch arc, it shows different combustion modes and movement modes. The modes have important influences on the success and failure of the vacuum switch. Therefore, studying the dynamic characteristics of the arc shape has important theoretical significance and useful value for improving the working performance and reliability of the vacuum switch. In this paper, the characteristics of the vacuum switch arc and particle motion parameters are studied. By studying and diagnosing the arc characteristics of the vacuum switch, the arc characteristics of a vacuum circuit breaker can be grasped from mechanism analyses and experiments.